The Relationship between BMI and Joint Inflammation Control Rheumatoid Arthritis - Al-foa'adi, Ala'a Hasan Jasim (Journal of Science in Medicine and Life, 2025)
Patient with the systemic autoimmune illness known as rheumatoid arthritis is brought on by a person`s immune system mistakenly attacking the joints' synovium, causing chronic damage to the joints. RA characterized by the inflammation of multiple joints and significant joint destruction and disability. Over time, joint inflammation causes bone erosion and cartilage loss, which at last leads to joint degeneration. Methods: current study used a descriptive quantitative design with an application of observation, study group approach to detect how body mass index connection as well as the joint inflammation for adult patients who are diagnosed with RA for 150 patients in Al-Diwaniyah, Al-Hamza, and Al-Shamiya public hospitals in Iraq. Participant's Body Mass Index measured as well as ESR were documented from laboratory test. Results: study reflect that the prevalence of joint inflammation was more in women than men. Also most of study sample suffering from overweight or obese for the most of sample that diagnosis with joint inflammation. Conclusions: A higher body mass index can raise the likelihood of developing joint inflammation. However, the finding also highlights the stand in need of research on the correlation between body mass index as well as joint inflammation risk with adjustment for more agitating factors.